2010
DOI: 10.1021/ef900613b
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon from Biomass for Mercury Capture: Effect of the Leaching Pretreatment on the Capture Efficiency

Abstract: Activated carbons were produced from two European biomasses such as olive residue and wheat straw. The leaching pretreatment is used to study the effect of chlorine and alkali metals on the mercury capture efficiency. The activated carbons were tested for mercury capture in a bench scale reactor against the commercial grade activated carbon NORIT DARCO Hg as well as an activated carbon developed at the Energy and Environmental Research Center (EERC) from lignite. The mercury capture tests showed that the untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Activated carbons (ACs) are widely used in many applications, such as solid adsorbents in pollutant adsorption and as electrodes in fuel cells, secondary batteries, and electrochemical capacitors. ACs are commonly produced from carbonaceous materials such as wood, coal, , and coconut shells. , In addition, they can be prepared from biomass wastes from agricultural and industrial processes. , Coal and coconut shells are commercially used as raw materials for AC preparation. However, since biomass wastes are generally inexpensive and abundant, their effective use is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbons (ACs) are widely used in many applications, such as solid adsorbents in pollutant adsorption and as electrodes in fuel cells, secondary batteries, and electrochemical capacitors. ACs are commonly produced from carbonaceous materials such as wood, coal, , and coconut shells. , In addition, they can be prepared from biomass wastes from agricultural and industrial processes. , Coal and coconut shells are commercially used as raw materials for AC preparation. However, since biomass wastes are generally inexpensive and abundant, their effective use is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The water-soluble elements in biomass have been studied widely (see refs , , , , , , , , , , , , , and ). It was found that the element proportions leached from different biomass sources are variable.…”
Section: Results and Ddscussionmentioning
confidence: 99%
“…The potential of technologies and improvements must be economically rational. Carbonaceous materials possess various advantages, including their surface area, favourable surface functionality, high chemical and thermal stability, environmentally feasible preparation methods, and cost-effective products [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The carbon derived from biomass mixed with metal/metal oxides/sulfides and other semiconductors possesses good photocatalytic activity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%